Gait improvements in the early post-surgery rehabilitation phase in subjects receiving a total knee or hip arthroplasty: A prospective study - Pollet, Joel; Pullara, Rosa; Bianchi, Luca N.C.; Falso, Maurizio V.; Gobbo, Massimiliano; Buraschi, Riccardo (Gait & posture, 2025)
Rehabilitation after total knee arthroplasty (TKA) and total hip arthroplasty (THA) is fundamental for reducing pain and recovering strength, range of motion, and walking ability. Gait analysis (GA) is rarely included in the rehabilitation path. This study assesses how inpatient rehabilitation influences clinical outcomes and gait analysis (GA) parameters in TKA and THA patients, comparing these with age- and speed-matched healthy subjects (HS). A prospective observational study included 80 subjects (50 TKA, 30 THA) and 20 aged-matched HS. Assessments occurred at admission and discharge post inpatient rehabilitation, using clinical outcome scales (e.g., Modified Barthel Index, Knee Society Score), GA spatiotemporal parameters, and gait summary measures (e.g., Gait Profile Score, Gait Deviation Index). Statistical analyses determined the significance of improvements. Post-rehabilitation, significant improvements were observed in clinical outcomes and some key spatio-temporal gait parameters (p ≤ 0.01). However, gait summary measures showed no changes. Interestingly, gait summary measures did not correlate with clinical outcome scales. Moreover, TKA and THA patients showed no differences compared with slow-walking HS. Inpatient rehabilitation significantly enhanced clinical outcomes and spatio-temporal parameters. Additionally, no differences were observed between spatiotemporal and gait summary measures of slow-walking HS and patients at discharge, indicating that rehabilitation restored gait quality. However, gait speed remains impaired, in both TKA and THA populations. Future research should explore personalized rehabilitation protocols to address these limitations and improve gait outcomes. Trial registration number. NCT04803578. •Rehabilitation significantly improved clinical outcomes and some gait parameters.•Clinical outcome scales did not correlate with gait quality.•Patients’ gait parameters at discharge were similar to slow-walking healthy subjects.